CONSTRUCTION TECHNOLOGY OF OPEN GRANITE STONE CURTAIN WALL - Lai PC; Yu Yabin; Wang Xiaoyan (Asosiasi Peneliti Sriwijaya, 2022)
This paper developed the self-locking back bolt fastener and the open stone curtain wall with waterproof function aimed for installation accuracy, connection structure stability, waterproof leakage, and earthquake resistance in constructing open granite stone curtain walls. The practice shows that applying this construction technology improves the stability and seismic performance of the curtain wall connection structure while also ensuring the stone curtain wall's waterproof and decorative properties.